Optimizing Solar Energy for Realizing Sustainable Energy Security in Sedalit, North Kalimantan - Bagus Joko Raharjo; M Sidik Boedoyo; Muliahadi Tumanggor (International Journal of Technology and Education Research, 2026)
Energy resilience, defined as the ability of a region to meet its energy needs independently and sustainably, has become a strategic issue, particularly in remote areas that are not yet optimally served by conventional electricity networks. Sedalit Village in North Kalimantan represents one of the regions with significant potential for the development of renewable energy to strengthen local energy independence and resilience. With an estimated 147 buildings and a population of approximately 400 people, the village hosts several essential public facilities, including three schools, two places of worship, three community halls, three government offices, one sports facility, two health posts (posyandu), and several other supporting infrastructures. A 52.8 kWp Solar Power Plant (PLTS) in Sedalit serves as a strategic solution for providing reliable, efficient, and environmentally friendly electricity supply. This study employs a quantitative method with an experimental approach to evaluate the performance of the off-grid solar power system in the area. The results show that the grounding system operates effectively, achieving the lowest resistance values ranging from 0.63 to 0.83 ohms. The inverter output remains stable at 219–220 V with a frequency of 50 Hz. Meanwhile, the DC input voltage varies between 456–502 V with a current of 0.60–0.84 A, indicating a slight decrease in performance across several solar module strings. Overall, the PLTS system in Sedalit demonstrates good operational performance and effectively supports sustainable energy supply.